Diffusion route planner: Data-driven modeling of human ship navigation that implicitly balances safety, efficiency, and rule compliance under complex geographical constraints - Takefumi Higaki; Hitoshi Yoshioka; Nobukazu Wakabayashi; Hirotada Hashimoto (Ocean Engineering, 2026)

First report of the whole-genome sequence analysis of avian rotavirus A from Japanese chickens - Ayana Okamoto; Hitoshi Takemae; Makoto Nagai; Shinichiro Hashimoto; Tetsuya Mizutani; Tetsuya Furuya (Virus Genes, 2024)

Decision-making algorithm for ship collision avoidance with collision risk map - Hitoshi Yoshioka; Hirotada Hashimoto; Hidenari Makino (Ocean Engineering, 2023)

Hydrologic-geotechnical modelling of shallow landslide and flood hazards caused by heavy rainfall - Nilo Lemuel J. Dolojan; Shuji Moriguchi; Masakazu Hashimoto; Nguyen Xuan Tinh; Hitoshi Tanaka; Kenjiro Terada (Engineering Geology, 2023)

Real-time deep neural network-based automatic bowel gas segmentation on X-ray images for particle beam treatment - Toshio Kumakiri; Shinichiro Mori; Yasukuni Mori; Ryusuke Hirai; Ayato Hashimoto; Yasuhiko Tachibana; Hiroki Suyari; Hitoshi Ishikawa (Physical and Engineering Sciences in Medicine, 2023)

The Pivotal Role of Neuropeptide Crosstalk from Ventromedial-PACAP to Dorsomedial-Galanin in the Appetite Regulation in the Mouse Hypothalamus - Yuki Kambe; Thanh Trung Nguyen; Toshiharu Yasaka; Thu Thi Nguyen; Yoshimune Sameshima; Kohei Hashiguchi; Norihito Shintani; Hitoshi Hashimoto; Takashi Kurihara; Atsuro Miyata (Molecular Neurobiology, 2023)

Influence of acute beetroot juice supplementation on cold-induced vasodilation and fingertip rewarming - Hitoshi Wakabayashi; Koji Sugiyama; Shinichi Suzuki; Yasuko Sakihama; Makoto Hashimoto; Martin J. Barwood (European Journal of Applied Physiology, 2022)

Effects of ABCB1 and ABCG2 polymorphisms on the pharmacokinetics of abemaciclib - Akimitsu Maeda; Hitoshi Ando; Kei Irie; Naoya Hashimoto; Jun-ichi Morishige; Shoji Fukushima; Akira Okada; Hiromichi Ebi; Masahide Matsuzaki; Hiroji Iwata; Masataka Sawaki (European Journal of Clinical Pharmacology, 2022)

The Protective Effects of Endogenous PACAP in Oxygen-Induced Retinopathy - Timea Kvarik; Dora Reglodi; Dora Werling; Alexandra Vaczy; Petra Kovari; Edina Szabo; Krisztina Kovacs; Hitoshi Hashimoto; Tibor Ertl; Judit Gyarmati; Tamas Atlasz (Journal of Molecular Neuroscience, 2021)
Pituitary adenylate cyclase–activating polypeptide (PACAP) is a neuropeptide having trophic and protective functions in neural tissues, including the retina. Previously, we have shown that intravitreal PACAP administration can maintain retinal structure in the animal model of retinopathy of prematurity (ROP). The purpose of this study is to examine the development of ROP in PACAP-deficient and wild-type mice to reveal the function of endogenous PACAP. Wild-type and PACAP-knockout (KO) mouse pups at postnatal day (PD) 7 were maintained at 75% oxygen for 5 consecutive days then returned to room air on PD12 to develop oxygen-induced retinopathy (OIR). On PD15, animals underwent electroretinography (ERG) to assess visual function. On PD16, eyes were harvested for either immunohistochemistry to determine the percentage of the central avascular retinal area or molecular analysis to assess angiogenesis proteins by array kit and anti-apoptotic protein kinase B (Akt) change by western blot. Retinas of PACAP-deficient OIR mice showed a greater central avascular area than that of the wild types. ERG revealed significantly decreased b-wave amplitude in PACAP KO compared to their controls. Several angiogenic proteins were upregulated due to OIR, and 11 different proteins markedly increased in PACAP-deficient mice, whereas western blot analysis revealed a reduction in Akt phosphorylation, suggesting an advanced cell death in the lack of PACAP. This is the first study to examine the endogenous effect of PACAP in the OIR model. Previously, we have shown the beneficial effect of exogenous local PACAP treatment in the rat OIR model. Together with the present findings, we suggest that PACAP could be a novel retinoprotective agent in ROP.

Two new triterpenoids from the leaves and stems of Lantana camara - Masateru Ono; Asami Hashimoto; Mayu Miyajima; Aimi Sakata; Chisato Furusawa; Mizuki Shimode; Shuhei Tsutsumi; Shin Yasuda; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2021)

Pituitary Adenylate Cyclase-Activating Polypeptide in the Ventromedial Hypothalamus Is Responsible for Food Intake Behavior by Modulating the Expression of Agouti-Related Peptide in Mice - Thanh Trung Nguyen; Yuki Kambe; Takashi Kurihara; Tomoya Nakamachi; Norihito Shintani; Hitoshi Hashimoto; Atsuro Miyata (Molecular Neurobiology, 2020)

Risperidone and aripiprazole alleviate prenatal valproic acid-induced abnormalities in behaviors and dendritic spine density in mice - Yuta Hara; Yukio Ago; Atsuki Taruta; Shigeru Hasebe; Haruki Kawase; Wataru Tanabe; Shinji Tsukada; Takanobu Nakazawa; Hitoshi Hashimoto; Toshio Matsuda; Kazuhiro Takuma (Psychopharmacology, 2017)

PACAP Protects the Adolescent and Adult Mice Brain from Ethanol Toxicity and Modulates Distinct Sets of Genes Regulating Similar Networks - Hélène Lacaille; Dominique Duterte-Boucher; Hubert Vaudry; Yasmine Zerdoumi; Jean-Michel Flaman; Hitoshi Hashimoto; David Vaudry (Molecular Neurobiology, 2017)

Early Neurobehavioral Development of Mice Lacking Endogenous PACAP - Jozsef Farkas; Balazs Sandor; Andrea Tamas; Peter Kiss; Hitoshi Hashimoto; Andras D. Nagy; Balazs D. Fulop; Tamas Juhasz; Sridharan Manavalan; Dora Reglodi (Journal of Molecular Neuroscience, 2017)

Involvement of GABAA receptors in 5-HT1A and σ1 receptor synergism on prefrontal dopaminergic transmission under circulating neurosteroid deficiency - Yukio Ago; Shigeru Hasebe; Naoki Hiramatsu; Kazuya Mori; Yuji Watabe; Yusuke Onaka; Hitoshi Hashimoto; Kazuhiro Takuma; Toshio Matsuda (Psychopharmacology, 2016)

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Is Involved in Adult Mouse Hippocampal Neurogenesis After Stroke - Minako Matsumoto; Tomoya Nakamachi; Jun Watanabe; Koichi Sugiyama; Hirokazu Ohtaki; Norimitsu Murai; Shun Sasaki; Zhifang Xu; Hitoshi Hashimoto; Tamotsu Seki; Akira Miyazaki; Seiji Shioda (Journal of Molecular Neuroscience, 2016)

Rivastigmine improves isolation rearing-induced prepulse inhibition deficits via muscarinic acetylcholine receptors in mice - Kosuke Higashino; Yukio Ago; Takahiro Umeki; Shigeru Hasebe; Yusuke Onaka; Hitoshi Hashimoto; Kazuhiro Takuma; Toshio Matsuda (Psychopharmacology, 2016)

Reductions in synaptic proteins and selective alteration of prepulse inhibition in male C57BL/6 mice after postnatal administration of a VIP receptor (VIPR2) agonist - Yukio Ago; Michael C. Condro; Yossan-Var Tan; Cristina A. Ghiani; Christopher S. Colwell; Jesse D. Cushman; Michael S. Fanselow; Hitoshi Hashimoto; James A. Waschek (Psychopharmacology, 2015)

Characterization of the Thermoregulatory Response to Pituitary Adenylate Cyclase-Activating Polypeptide in Rodents - Eszter Banki; Eszter Pakai; Balazs Gaszner; Csaba Zsiboras; Andras Czett; Paras Rahul Parkash Bhuddi; Hitoshi Hashimoto; Gabor Toth; Andrea Tamas; Dora Reglodi; Andras Garami (Journal of Molecular Neuroscience, 2014)

Effect of feeding rotifers enriched with taurine on the growth and survival of larval amberjack Seriola dumerili - Hiroyuki Matsunari; Hiroshi Hashimoto; Takashi Iwasaki; Kentaro Oda; Yoshitsugu Masuda; Hitoshi Imaizumi; Kazuhisa Teruya; Hirofumi Furuita; Takeshi Yamamoto; Kazuhisa Hamada; Keiichi Mushiake (Fisheries Science, 2013)

Distribution of Secretin Receptors in the Rat Central Nervous System: an in situ Hybridization Study - Zsuzsanna E. Tóth; Andrea Heinzlmann; Hitoshi Hashimoto; Katalin Köves (Journal of Molecular Neuroscience, 2013)

Serotonin 5-HT7 Receptor Blockade Reverses Behavioral Abnormalities in PACAP-Deficient Mice and Receptor Activation Promotes Neurite Extension in Primary Embryonic Hippocampal Neurons - Minako Tajiri; Atsuko Hayata-Takano; Kaoru Seiriki; Katsuya Ogata; Keisuke Hazama; Norihito Shintani; Akemichi Baba; Hitoshi Hashimoto (Journal of Molecular Neuroscience, 2012)

Intranasal Application of Secretin, Similarly to Intracerebroventricular Administration, Influences the Motor Behavior of Mice Probably Through Specific Receptors - Andrea Heinzlmann; Gusztáv Kiss; Zsuzsanna E. Tóth; Roberta Dochnal; Ágnes Pál; Ildikó Sipos; Máté Manczinger; Gyula Szabó; Hitoshi Hashimoto; Katalin Köves (Journal of Molecular Neuroscience, 2012)

Neuroprotective Effect of Endogenous Pituitary Adenylate Cyclase-Activating Polypeptide on Spinal Cord Injury - Daisuke Tsuchikawa; Tomoya Nakamachi; Masashi Tsuchida; Yoshihiro Wada; Motohide Hori; Jozsef Farkas; Akira Yoshikawa; Nobuyuki Kagami; Nori Imai; Norihito Shintani; Hitoshi Hashimoto; Takashi Atsumi; et al. (Journal of Molecular Neuroscience, 2012)

Compensatory Recovery of Blood Glucose Levels in KKAy Mice Fed a High-Fat Diet: Insulin-Sparing Effects of PACAP Overexpression in β Cells - Yusuke Sakurai; Hiroaki Inoue; Norihito Shintani; Akihiro Arimori; Ken-ichi Hamagami; Atsuko Hayata-Takano; Akemichi Baba; Hitoshi Hashimoto (Journal of Molecular Neuroscience, 2012)

Effect of different algae used for enrichment of rotifers on growth, survival, and swim bladder inflation of larval amberjack Seriola dumerili - Hiroyuki Matsunari; Hiroshi Hashimoto; Kentaro Oda; Yoshitsugu Masuda; Hitoshi Imaizumi; Kazuhisa Teruya; Hirofumi Furuita; Takeshi Yamamoto; Kazuhisa Hamada; Keiichi Mushiake (Aquaculture International, 2012)

Activation of metabotropic glutamate 2/3 receptors attenuates methamphetamine-induced hyperlocomotion and increase in prefrontal serotonergic neurotransmission - Yukio Ago; Ryota Araki; Koji Yano; Naoki Hiramatsu; Toshiyuki Kawasaki; Shigeyuki Chaki; Atsuro Nakazato; Hirotaka Onoe; Hitoshi Hashimoto; Akemichi Baba; Kazuhiro Takuma; Toshio Matsuda (Psychopharmacology, 2011)

Environmental regulation of stomatal response in the Arabidopsis Cvi-0 ecotype - Keina Monda; Juntaro Negi; Atsuhiro Iio; Kensuke Kusumi; Mikiko Kojima; Mimi Hashimoto; Hitoshi Sakakibara; Koh Iba (Planta, 2011)

Isolation of a Leptothrix Strain, OUMS1, from Ocherous Deposits in Groundwater - Michinori Sawayama; Tomoko Suzuki; Hideki Hashimoto; Tomonari Kasai; Mitsuaki Furutani; Naoyuki Miyata; Hitoshi Kunoh; Jun Takada (Current Microbiology, 2011)

Basin-Wide Distribution of Land Use and Human Population: Stream Order Modeling and River Basin Classification in Japan - Hitoshi Miyamoto; Tsubasa Hashimoto; Kohji Michioku (Environmental Management, 2011)

Neuroprotective Effect of PACAP Against NMDA-Induced Retinal Damage in the Mouse - Kimi Endo; Tomoya Nakamachi; Tamotsu Seki; Nobuyuki Kagami; Yoshihiro Wada; Keisuke Nakamura; Koji Kishimoto; Motohide Hori; Daisuke Tsuchikawa; Norihito Shinntani; Hitoshi Hashimoto; Akemichi Baba; et al. (Journal of Molecular Neuroscience, 2011)

Trophic Effects of PACAP on Pancreatic Islets: A Mini-Review - Yusuke Sakurai; Norihito Shintani; Atsuko Hayata; Hitoshi Hashimoto; Akemichi Baba (Journal of Molecular Neuroscience, 2011)

Cerulein-Induced Acute Pancreatitis in PACAP Knockout Mice - Yusuke Sakurai; Norihito Shintani; Akihiro Arimori; Ken-ichi Hamagami; Naoko Higuchi; Hiroaki Inoue; Kazuya Ikeda; Atsuko Hayata; Hitoshi Hashimoto; Akemichi Baba (Journal of Molecular Neuroscience, 2011)

Intra-Islet PACAP Protects Pancreatic β-Cells Against Glucotoxicity and Lipotoxicity - Masanori Nakata; Norihito Shintani; Hitoshi Hashimoto; Akemichi Baba; Toshihiko Yada (Journal of Molecular Neuroscience, 2010)

Pituitary Adenylate Cyclase-Activating Polypeptide Deficiency Enhances Oxazolone-Induced Allergic Contact Dermatitis in Mice - Ágnes Kemény; Dóra Reglődi; Renáta Cseharovszky; Hitoshi Hashimoto; Akemichi Baba; János Szolcsányi; Erika Pintér; Zsuzsanna Helyes (Journal of Molecular Neuroscience, 2010)

Regulation of Oxidative Stress by Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Mediated by PACAP Receptor - Hirokazu Ohtaki; Atsushi Satoh; Tomoya Nakamachi; Sachiko Yofu; Kenji Dohi; Hiroyoshi Mori; Kenji Ohara; Kazuyuki Miyamoto; Hitoshi Hashimoto; Norihito Shintani; Akemichi Baba; Masaji Matsunaga; et al. (Journal of Molecular Neuroscience, 2010)

Presence of Endogenous PACAP-38 Ameliorated Intestinal Cold Preservation Tissue Injury - Andrea Ferencz; Gyorgy Weber; Zsuzsanna Helyes; Hitoshi Hashimoto; Akemichi Baba; Dora Reglodi (Journal of Molecular Neuroscience, 2010)

Galantamine and donepezil differently affect isolation rearing-induced deficits of prepulse inhibition in mice - Ken Koda; Yukio Ago; Toshiyuki Kawasaki; Hitoshi Hashimoto; Akemichi Baba; Toshio Matsuda (Psychopharmacology, 2008)

Chromone and flavonol glycosides from Delphinium hybridum cv. “Belladonna Casablanca” - Hitoshi Yoshimitsu; Makiko Nishida; Fumio Hashimoto; Mika Tanaka; Yusuke Sakata; Masafumi Okawa; Toshihiro Nohara (Journal of Natural Medicines, 2007)

Phylogenetic analysis of the genus Petunia (Solanaceae) based on the sequence of the Hf1 gene - Sumei Chen; Kiyoshi Matsubara; Takahiro Omori; Hisashi Kokubun; Hiroaki Kodama; Hitoshi Watanabe; Goro Hashimoto; Eduardo Marchesi; Laura Bullrich; Toshio Ando (Journal of Plant Research, 2007)

Distribution of self-compatible and self-incompatible populations of Petunia axillaris (Solanaceae) outside Uruguay - Hisashi Kokubun; Makoto Nakano; Tatsuya Tsukamoto; Hitoshi Watanabe; Goro Hashimoto; Eduardo Marchesi; Laura Bullrich; Isabel L. Basualdo; Teh-hui Kao; Toshio Ando (Journal of Plant Research, 2006)

Roles of PACAP and PHI as inhibitory neurotransmitters in the circular muscle of mouse antrum - Makiko Toyoshima; Tadayoshi Takeuchi; Hiroto Goto; Kazunori Mukai; Norihito Shintani; Hitoshi Hashimoto; Akemichi Baba; Fumiaki Hata (Pflügers Archiv - European Journal of Physiology, 2006)

The possible role of zinc and metallothionein in the liver on the therapeutic effect of IFN-α to hepatitis C patients - Takeaki Nagamine; Hitoshi Takagi; Yoshiaki Hashimoto; Hisashi Takayama; Ryuya Shimoda; Naruo Nomura; Keiji Suzuki; Masatomo Mori; Katsuyuki Nakajima (Biological Trace Element Research, 1997)